Boosting Photoacoustic Effect via Intramolecular Motions Amplifying Thermal‐to‐Acoustic Conversion Efficiency for Adaptive Image‐Guided Cancer Surgery. Issue 38 (13th August 2021) - Gao, Heqi; Duan, Xingchen; Jiao, Di; Zeng, Yi; Zheng, Xiaoyan; Zhang, Jingtian; Ou, Hanlin; Qi, Ji; Ding, Dan
Abstract: Photoacoustic (PA) imaging emerges as a promising technique for biomedical applications. The development of new strategies to boost PA conversion without depressing other properties (e.g., fluorescence) is highly desirable for multifunctional imaging but difficult to realize. Here, we report a new phenomenon that active intramolecular motions could promote PA signal by specifically increasing thermal‐to‐acoustic conversion efficiency. The compound with intense intramolecular motion exhibits amplified PA signal by elevating thermal‐to‐acoustic conversion, and the fluorescence also increases due to aggregation‐induced emission signature. The simultaneously high PA and fluorescence brightness of TPA‐TQ3 NPs enable precise image‐guided surgery. The preoperative fluorescence and PA imaging are capable of locating orthotopic breast tumor in a high‐contrast manner, and the intraoperative fluorescence imaging delineates tiny residual tumors. This study highlights a new design guideline of intramolecular motion amplifying PA effect. Abstract : A compound with intense intramolecular motions exhibits an amplified photoacoustic signal by specifically elevating the thermal‐to‐acoustic conversion efficiency, and the fluorescence brightness also increases due to the aggregation‐induced emission signature. Precise in vivo image‐guided cancer surgery in different stages is conducted, greatly boosting the surgery outcome.